THE IMPACT OF FINANCIAL RATIOS ON STOCK RETURN: EVIDENCE FROM RETAIL COMPANY LISTED IN INDONESIA STOCK EXCHANGE DURING 2011-2013 - Stephen Christian (iBuss Management, 2015)
Indonesia is one of the biggest economies in the world, proven by its involvement in G20. Not only that, Indonesia Stock Exchange is also attractive for the investor. In opening of 2013, Jakarta Composite Index positioned themselves in 4,316.69 and increased to 5,214.98 only in five months, highest position ever. Retail industry is also a promising industry in Indonesia given the fact that the sales in 2014 is 178% of 2010 sales. Given all of the facts, there might be many investor that is interested in investing in retail industry in Indonesia. However, they need to adapt some tools to help them understand the unpredictable movement of stock market.This research tries to predict the stock return by using three financial ratios, which are price earnings ratio, dividend yield, and book to market ratio. This research will use multiple linear regression to test the hypothesis by including all of the population available. The result of this research conclude that price earnings ratio, dividend yield, and book to market ratio has significant effect on stock return simultaneously whereas, only dividend yield is the only ratio that might predict the stock return individually. Keywords: Financial ratio, stock return, retail company, Jakarta stock exchange.